Resin composition, molded product and method for producing molded product
The resin composition with optimized spherical and fibrous fillers addresses the issue of uneven surfaces and peeling in molded products by reducing linear expansion coefficients, ensuring high-quality and durable molded products.
Patent Information
- Application Number
- JP2023116988
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-18
- Publication Date
- 2025-01-30
AI Technical Summary
Molded products using thermoplastic resin often experience peeling and gaps due to large differences in linear expansion coefficients between materials, leading to uneven surfaces and increased costs for polishing to improve appearance.
A resin composition comprising thermoplastic resin, spherical silica with different average particle diameters, and fibrous filler is used, where the ratio and content of these components are optimized to reduce the linear expansion coefficient and maintain mechanical strength and appearance.
The resin composition achieves a low linear expansion coefficient, excellent appearance, and improved molding, resulting in high-quality molded products suitable for applications with large temperature changes.
Smart Images

Figure 2025014439000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a resin composition that can be suitably used for injection molding, etc., a molded article, and a method for producing the molded article. [Background technology]
[0002] Molded products using thermoplastic resins are used in many fields, including automotive products, electrical and electronic products, mechanical products, medical products, household products, etc. These molded products are sometimes composited with other materials such as glass, ceramics, and metals, but if there is a large difference in the linear expansion coefficient between the materials, problems such as peeling and gaps can occur at the boundary between them when used in an environment with large temperature changes.
[0003] A method of adding a filler to a resin is known as a method of adjusting the linear expansion coefficient of a resin molded product. Patent Document 1 describes a molding material that contains (A) resin, (B1) fibrous filler, and (B2) spherical filler, and in which the average particle size of the (B2) spherical filler is in the range of 2.5d to 6.5d when the number average fiber diameter of the (B1) fibrous filler is d. It also describes that by using a specific spherical filler, the fibrous filler can be randomly arranged in the gaps between the appropriately dispersed spherical fillers, and as a result, it is believed that the occurrence of anisotropy as a molded product can be suppressed.
[0004] However, the surface of a molded product obtained by molding the molding material, particularly a molded product obtained by injection molding, may have irregularities or sink marks due to the fibrous filler or spherical filler, which may cause problems in appearance. Furthermore, when such a molded product is painted, bumps and unevenness may occur in the paint film, and polishing is required to improve the appearance, which increases costs. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2016-088987 A Summary of the Invention [Problem to be solved by the invention]
[0006] The present invention has been made to solve the above problems, and an object of the present invention is to provide a resin composition that has a small linear expansion coefficient in the machine direction (MD), can give a molded article with excellent appearance, and has excellent moldability. [Means for solving the problem]
[0007] The above problem is solved by providing a resin composition containing 100 parts by mass of a thermoplastic resin (A), 3 to 150 parts by mass of a spherical filler (B), and 3 to 100 parts by mass of a fibrous filler (C), in which the spherical filler (B) consists of spherical silica (B1) having an average particle diameter D1 of 1 to 10 μm and spherical silica (B2) having an average particle diameter D2 of 0.1 to 3 μm, the ratio (D1 / D2) of the average particle diameter D1 (μm) to the average particle diameter D2 (μm) being 2 or more, and the mass ratio (B1 / B2) of the spherical silica (B1) to the spherical silica (B2) being 10 / 90 to 90 / 10.
[0008] In this case, it is preferable that the fibrous filler (C) is at least one selected from the group consisting of glass fiber and carbon fiber. A molded article obtained by injection molding the resin composition is a preferred embodiment of the present invention. In this case, it is preferable that the linear expansion coefficient of the molded article in the machine direction (MD) is 40 ppm / °C or less. It is also preferable that the molded article is for automobiles. A composite obtained by combining the molded article with at least one member selected from the group consisting of glass, ceramics, and metal is a more preferred embodiment of the present invention. An in-vehicle monitor using the composite is a further preferred embodiment of the present invention.
[0009] A method for producing a molded article by injection molding the resin composition is also a preferred embodiment of the present invention. A more preferred embodiment of the present invention is a method for producing a composite article by injection molding the resin composition to obtain a molded article, and then combining the molded article with a member made of at least one material selected from the group consisting of glass, ceramics, and metal. Effect of the Invention
[0010] The resin composition of the present invention has excellent moldability, a small coefficient of linear expansion in the machine direction (MD), and can give molded articles with excellent appearance. Moreover, the resin composition has excellent moldability. [Brief description of the drawings]
[0011] [Figure 1] FIG. 1 is a diagram showing molded articles for automobile interiors in Examples 1 to 3 and Comparative Examples 1 to 7. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] The resin composition of the present invention contains 100 parts by mass of a thermoplastic resin (A), 3 to 150 parts by mass of a spherical filler (B), and 3 to 100 parts by mass of a fibrous filler (C), the spherical filler (B) being composed of spherical silica (B1) having an average particle diameter D1 of 1 to 10 μm and spherical silica (B2) having an average particle diameter D2 of 0.1 to 3 μm, the ratio (D1 / D2) of the average particle diameter D1 (μm) to the average particle diameter D2 (μm) being 2 or more, and the mass ratio (B1 / B2) of the spherical silica (B1) to the spherical silica (B2) being 10 / 90 to 90 / 10. Such a resin composition has excellent moldability, a small linear expansion coefficient in the machine direction (MD), and can give a molded product having excellent appearance.
[0013] The thermoplastic resin (A) is not particularly limited as long as it is melt moldable, and examples thereof include polycarbonate resin, ABS resin, urethane resin, chlorotrifluoroethylene resin, tetrafluoroethylene-hexafluoropropylene copolymer, tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer, vinylidene fluoride resin, ethylene-tetrafluoroethylene copolymer, ethylene-chlorofluoroethylene copolymer, vinyl chloride resin, chlorine-diphenyl ether resin, polyethylene, polypropylene, chlorinated polyolefin, water-crosslinked polyolefin, modified polyolefin, ethylene-vinyl acetate copolymer, ethylene-ethyl acrylate copolymer, polystyrene, polyamide, methacrylic resin, polyacetal, cellulose-based resin, polyvinyl alcohol, polyurethane elastomer, polyimide, polyetherimide, polyamideimide, ionomer resin, polyphenylene Examples of the resin include polyvinyl chloride, ... Alloys of polycarbonate resin and ABS resin are sold, for example, by Techno UMG Co., Ltd. under the trade name "HUSHLLOY" and by Teijin Limited under the trade name "Multilon", and it is possible to easily obtain and use commercially available products.As the polycarbonate resin, commercially available products such as "Iupilon" manufactured by Mitsubishi Engineering Plastics Corporation and "Panlite" manufactured by Teijin Limited can be used.
[0014] The spherical filler (B) is composed of spherical silica (B1) having an average particle diameter D1 of 1 to 10 μm and spherical silica (B2) having an average particle diameter D2 of 0.1 to 3 μm. In this way, by adding two types of spherical silica (B1) and spherical silica (B2) having different average particle diameters to the thermoplastic resin (A) together with the fibrous filler (C) described later, the linear expansion coefficient in the machine direction (MD) can be reduced without impairing the appearance of the obtained molded article. Moreover, the resin composition of the present invention has excellent moldability, and the obtained molded article has excellent mechanical strength. The reason for this is not clear, but the following is considered. When the present inventors added the fibrous filler (C) to the thermoplastic resin (A) in order to reduce the linear expansion coefficient in the machine direction (MD), unevenness resulting from the fibrous filler (C) occurred on the surface of the molded article. In addition, although the linear expansion coefficient is generally reduced by increasing the content of the filler added to the resin, the fluidity of the resin composition is reduced, and the moldability is reduced, or the molded product becomes brittle and the mechanical strength is reduced. In addition, the appearance may also be deteriorated. On the other hand, when spherical silica (B1) and spherical silica (B2) having different average particle sizes are added to the thermoplastic resin (A) together with the fibrous filler (C), the linear expansion coefficient in the flow direction (MD) can be reduced while maintaining the moldability and mechanical strength. It is considered that the spherical silica (B1), spherical silica (B2), and fibrous filler (C) are filled in a dispersed state even when the content of the spherical silica (B1), spherical silica (B2), and fibrous filler (C) is high, by filling the gaps between the spherical silica (B1) and fibrous filler (C) having a large average particle size with the spherical silica (B2) having a small average particle size. As a result, it is considered that the linear expansion coefficient in the flow direction (MD) can be reduced while maintaining the mechanical strength of the obtained molded product, and warping can also be suppressed. In addition, by including a certain amount of spherical silica (B1) having a large average particle size, the flowability of the resin composition is improved, which is believed to improve moldability. Furthermore, the fine spherical silica (B2) is present on the surface together with the fibrous filler (C), and this spherical silica (B2) is believed to suppress the occurrence of unevenness due to sink marks in the resin near the fibrous filler (C), thereby obtaining a molded product with a good appearance.In particular, when injection molding is performed, unevenness is likely to occur due to the fibrous filler (C), but it is believed that the uniform distribution of the spherical silica (B2) in the vicinity of the fibrous filler (C) effectively smoothes the surface.
[0015] The content of the spherical filler (B) in the resin composition is 3 to 150 parts by mass relative to 100 parts by mass of the thermoplastic resin (A). When the content of the spherical filler (B) is 3 parts by mass or more, the linear expansion coefficient in the machine direction (MD) of the obtained molded article is reduced and the appearance is improved. The content of the spherical filler (B) is preferably 5 parts by mass or more, more preferably 8 parts by mass or more, even more preferably 10 parts by mass or more, and particularly preferably 11 parts by mass or more. On the other hand, when the content of the spherical filler (B) is 150 parts by mass or less, the mechanical strength of the obtained molded article is improved and the moldability is improved. The content of the spherical filler (B) is preferably 100 parts by mass or less, more preferably 80 parts by mass or less, even more preferably 60 parts by mass or less, even more preferably 50 parts by mass or less, particularly preferably 35 parts by mass or less, and most preferably 25 parts by mass or less.
[0016] The average particle diameter D1 of the spherical silica (B1) must be 1 to 10 μm. When the average particle diameter D1 is 1 μm or more, the flowability of the resin composition is improved, the moldability is improved, and the linear expansion coefficient in the machine direction (MD) of the obtained molded article is reduced. The average particle diameter D1 is preferably 1.2 μm or more, more preferably 1.5 μm or more, and even more preferably 1.7 μm or more. On the other hand, when the average particle diameter D1 is 10 μm or less, the appearance of the obtained molded article is good. The average particle diameter D1 is preferably 8 μm or less, more preferably 5 μm or less, even more preferably 3 μm or less, and particularly preferably 2.5 μm or less. The average particle diameter of the spherical silica and the average particle diameter of the spherical silica fine particles are determined by a laser diffraction / scattering method using a laser analysis type particle size distribution meter.
[0017] The average particle diameter D2 of the spherical silica (B2) must be 0.1 to 3 μm. When the average particle diameter D2 is 0.1 μm or more, the surface condition of the obtained molded article and the appearance after painting of the molded article are improved. The average particle diameter D2 is preferably 0.2 μm or more, more preferably 0.3 μm or more, and even more preferably 0.4 μm or more. On the other hand, when the average particle diameter D2 is 3 μm or less, the linear expansion coefficient in the machine direction (MD) of the obtained molded article is reduced and the appearance is improved. The average particle diameter D2 is preferably 2.5 μm or less, more preferably 2 μm or less, even more preferably 1.5 μm or less, even more preferably 1 μm or less, and particularly preferably 0.8 μm or less.
[0018] The ratio (D1 / D2) of the average particle diameter D1 (μm) to the average particle diameter D2 (μm) must be 2 or more. This reduces the linear expansion coefficient in the machine direction (MD) of the resulting molded article, and improves the mechanical strength. Furthermore, the appearance of the resulting molded article is improved. The ratio (D1 / D2) is preferably 2.5 or more, more preferably 3. Meanwhile, the ratio (D1 / D2) is usually 50 or less, preferably 20 or less, and more preferably 10 or less.
[0019] The mass ratio (B1 / B2) of the spherical silica (B1) to the spherical silica (B2) must be 10 / 90 to 90 / 10. When the mass ratio (B1 / B2) is 10 / 90 or more, the linear expansion coefficient in the machine direction (MD) of the obtained molded article is reduced, and the mechanical properties are improved. Furthermore, the flowability of the resin composition is improved, and the moldability is improved. The mass ratio (B1 / B2) is preferably 20 / 80 or more, more preferably 30 / 70 or more, even more preferably 40 / 60 or more, even more preferably 50 / 50 or more, and particularly preferably 60 / 40 or more. On the other hand, when the mass ratio (B1 / B2) is 90 / 10 or less, the linear expansion coefficient in the machine direction (MD) of the obtained molded article is reduced, and the mechanical strength is improved. Furthermore, the appearance of the obtained molded article is good. The mass ratio (B1 / B2) is preferably 85 / 15 or less, and more preferably 80 / 20 or less.
[0020] The specific surface area S1 of spherical silica (B1) is 0.5 to 3 m2 / g is preferable. The specific surface area of the spherical silica is a value measured by the BET method using nitrogen. When the specific surface area S1 of the spherical silica (B1) is in such a range, the fluidity of the resin composition is further improved, and the moldability is improved. The specific surface area S1 is preferably 2.5 m 2 / g or less is more preferable.
[0021] The specific surface area S2 of spherical silica (B2) is 2 to 20 m 2 When the specific surface area S2 of the spherical silica (B2) is in this range, the fluidity of the resin composition is further improved, and the moldability is improved. 2 On the other hand, the specific surface area S2 is preferably 15 m 2 / g is more preferable, and 10m 2 / g is more preferred.
[0022] Specific surface area S2(m 2 / g) to the specific surface area S1 (m 2 It is preferable that the ratio (S1 / S2) of the linear expansion coefficient in the machine direction (MD) of the obtained molded article is 0.8 or less. This further reduces the linear expansion coefficient in the machine direction (MD) of the obtained molded article, and further improves the mechanical strength. Furthermore, the appearance of the obtained molded article is further improved. The ratio (S1 / S2) is more preferably 0.5 or less, still more preferably 0.4 or less, and particularly preferably 0.35 or less. On the other hand, the ratio (D1 / D2) is usually 0.05 or more, preferably 0.1 or more, and more preferably 0.15 or more.
[0023] The method for producing the spherical silica (B1) and (B2) is not particularly limited, and for example, a method in which a chemical flame is formed by a burner in an atmosphere containing oxygen, a metal powder that forms part of the target oxide fine particles is added into the chemical flame in an amount sufficient to form a dust cloud, and oxide fine particles are obtained by causing a deflagration, i.e., a vaporized metal combustion method (VMC method), etc., is adopted. As the VMC method, the method described in JP-A-60-255602, etc. is adopted. In addition, the spherical silica obtained by such a method is sold, for example, by Admatechs Co., Ltd. under the trade name "Admafine" and by Nippon Shokubai Co., Ltd. under the name "Seahoster", etc., and it is easy to obtain a commercially available product.
[0024] From the viewpoint of compatibility with the thermoplastic resin (A), it is preferable to subject the spherical silica (B1) or the spherical silica (B2) to a surface treatment. As the surface treatment method, a general silica surface treatment method can be adopted, for example, a method of treating the spherical silica (B1) or the spherical silica (B2) with a surface treatment agent such as organosilane or vinylsilane.
[0025] Next, the fibrous filler (C) contained in the resin composition will be described. As the fibrous filler (C) used in the present invention, either inorganic or organic fibers can be used. Examples of inorganic fibers include carbon fibers, glass fibers, basic magnesium sulfate fibers (such as "MOS HIGE" manufactured by Ube Materials, Ltd.), potassium titanate fibers (such as "TISM" manufactured by Otsuka Chemical Co., Ltd.), and carbon nanotubes. Examples of organic fibers include organic fibers such as fully aromatic polyester fibers, aramid fibers, and cellulose nanofibers. The fibrous filler (C) is preferably an inorganic fiber, and more preferably at least one selected from the group consisting of glass fibers and carbon fibers. By including such a fibrous filler (C) in the resin composition, the linear expansion coefficient in the machine direction (MD) of the obtained molded product is reduced, and the mechanical strength is improved.
[0026] The average length of the fibrous filler (C) is preferably 0.1 to 20 mm. When the average length is 0.1 mm or more, the linear expansion coefficient in the machine direction (MD) of the obtained molded article is further reduced, and the mechanical properties are further improved. The average length is more preferably 0.5 mm or more, more preferably 1 mm or more, even more preferably 2 mm or more, particularly preferably 4 mm or more, and most preferably 5 mm or more. On the other hand, when the average length is 20 mm or less, the moldability is further improved. The average length is more preferably 15 mm or less, more preferably 10 mm or less, and particularly preferably 8 mm or less. The average length and average diameter of the fibrous filler (C) are measured by observing the cross section of the molded article with a microscope or electron microscope. In this case, the aspect ratio (fiber length / fiber diameter) is preferably 10 or more.
[0027] The average diameter of the fibrous filler (C) is preferably 0.1 to 50 μm. When the average diameter is 0.1 μm or more, the linear expansion coefficient in the machine direction (MD) of the obtained molded article is further reduced, and the mechanical properties are further improved. The average diameter is more preferably 0.5 μm or more. On the other hand, when the average diameter is 50 μm or less, the appearance of the obtained molded article is further improved. The average diameter is more preferably 30 μm or less.
[0028] The content of the fibrous filler (C) in the resin composition is 3 to 100 parts by mass relative to 100 parts by mass of the thermoplastic resin (A). When the content of the fibrous filler (C) is 3 parts by mass or more, the linear expansion coefficient in the machine direction (MD) of the obtained molded article is reduced, and the mechanical strength is improved. The content of the fibrous filler (C) is preferably 5 parts by mass or more, more preferably 10 parts by mass or more, even more preferably 20 parts by mass or more, particularly preferably 25 parts by mass or more, and most preferably 30 parts by mass or more. On the other hand, when the content of the fibrous filler (C) is 100 parts by mass or less, the appearance of the obtained molded article is good, and the moldability is good. The content of the fibrous filler (C) is preferably 80 parts by mass or less, more preferably 70 parts by mass or less, even more preferably 50 parts by mass or less, even more preferably 45 parts by mass or less, and particularly preferably 40 parts by mass or less.
[0029] From the viewpoints of further reducing the linear expansion coefficient in the machine direction (MD) of the obtained molded article and further improving the appearance, the total content of the thermoplastic resin (A), the spherical filler (B), and the fibrous filler (C) in the resin composition is preferably 60 mass% or more, more preferably 80 mass% or more, even more preferably 90 mass% or more, and particularly preferably 95 mass% or more.
[0030] The resin composition may contain other components other than the thermoplastic resin (A), the spherical filler (B), and the fibrous filler (C) as long as the effects of the present invention are not impaired. The content of the other components is preferably 40% by mass or less, more preferably 20% by mass or less, even more preferably 10% by mass or less, and particularly preferably 5% by mass or less. Examples of the other components include dispersants, plasticizers, stabilizers, surfactants, colorants, ultraviolet absorbers, antistatic agents, crosslinking agents, etc.
[0031] From the viewpoint of further improving moldability, particularly injection moldability, the melt flow rate (MFR, 230°C, load 98N) of the resin composition is preferably 1 g / 10 min or more, more preferably 3 g / 10 min or more, and particularly preferably 5 g / 10 min or more. On the other hand, from the viewpoint of moldability, the MFR is preferably 100 or less.
[0032] The method for producing the resin composition is not particularly limited, and examples thereof include a method in which the thermoplastic resin (A), the spherical filler (B), the fibrous filler (C), and, if necessary, the other components are mixed and then melt-kneaded. The melt-kneading can be carried out using a known mixing or kneading device such as an extruder, a kneader-ruder, a mixing roll, or a Banbury mixer. The temperature during melt-kneading is usually 100 to 300°C.
[0033] By using the resin composition thus obtained, a molded article having a low linear expansion coefficient in the machine direction (MD), good appearance, and excellent mechanical strength can be obtained. Moreover, the resin composition has excellent moldability. Therefore, the resin composition can be used as a material for various molded articles. A molded article made of the resin composition is a preferred embodiment of the present invention. The molded article can be suitably used for a wide range of applications, such as automobiles, electrical and electronics, machinery, medical, and household applications.
[0034] Among them, it is also preferable that the molded article is for automobiles. As described above, the molded article has a low linear expansion coefficient in the machine direction (MD), a good appearance, and excellent mechanical strength. Therefore, the molded article is preferably used in an environment with large temperature changes. Such molded articles for automobiles include molded articles for automobile interiors, molded articles for exteriors such as bumpers, engine covers, etc., and molded articles for automobile interiors are preferred. Examples of the molded articles for automobile interiors include panels for in-vehicle monitors, door trims, and speedometer panels.
[0035] As a molding method of the resin composition, any method such as injection molding, extrusion molding, press molding, blow molding, calendar molding, vacuum molding, etc. can be adopted, among which injection molding is preferable. An injection molded product made of the resin composition is also a preferred embodiment of the present invention. As mentioned above, when injection molding is performed, unevenness due to the fibrous filler (C) is likely to occur, but the surface is effectively smoothed by using the spherical silica (B2), so there is a great advantage in using the resin composition of the present invention.
[0036] The resin composition may be injection-molded, for example, by injecting the resin composition into a cavity formed in a mold to fill it. The molding conditions during injection molding may be appropriately adjusted depending on the type of thermoplastic resin (A) and are not particularly limited, but it is preferable to mold the resin composition at a cylinder temperature of 100 to 330°C.
[0037] The linear expansion coefficient in the machine direction (MD) of the molded article made of the resin composition thus obtained is preferably 40 ppm / ° C. or less. Since such a molded article has a linear expansion coefficient close to that of a member made of glass or the like described below, peeling or gaps are unlikely to occur when combined with the member. The linear expansion coefficient is more preferably 35 ppm / ° C. or less, even more preferably 28 ppm / ° C. or less, even more preferably 25 ppm / ° C. or less, particularly preferably 20 ppm / ° C. or less, and most preferably 15 ppm / ° C. or less.
[0038] The surface of the molded article may be painted or plated. Examples of the painting method include spray painting, brush painting, electrodeposition painting, electrostatic painting, and ultraviolet curing painting. Paints that are generally used for resin painting are used, and examples of the paint include acrylic urethane paint. The thickness of the coating film formed on the surface of the molded article is usually 1 to 100 μm. Examples of plating include electroplating, electroless plating, and vapor deposition. A film may also be laminated on the surface of the front panel. Examples of the film used in this case include an anti-glare film (anti-reflection film) and an anti-finger film (film for preventing fingerprints).
[0039] In addition, a composite of the molded product and another member made of a material other than resin, specifically, a composite of the molded product and at least one member selected from the group consisting of glass, ceramics, and metal, is also a more preferred embodiment of the present invention. The linear expansion coefficient of the molded product in the machine direction (MD) can be reduced to be close to the linear expansion coefficient of the other member, thereby suppressing peeling and gaps at the boundary of the composite. The other member is preferably glass. The molded product and the other member may be in direct contact with each other, or may be composited via a double-sided tape, adhesive, or the like. Examples of the metal include aluminum, aluminum alloy, magnesium, magnesium alloy, and titanium.
[0040] The method for producing the composite is not particularly limited, but a method in which a molded article is obtained by injection molding the resin composition, and then the molded article is combined with the other member is preferable. At this time, the molded article and the other member may be bonded via a double-sided tape or an adhesive. The composite can also be produced by insert molding. Here, insert molding is a molding method in which the resin composition is injected so as to contact the surface of the other member mounted in a mold, and the resin composition is filled in the cavity to integrate the member and the resin composition.
[0041] Such composites are used for various purposes, and are particularly suitable for use in vehicle-mounted monitors and the like. EXAMPLES
[0042] The present invention will now be described in more detail with reference to examples.
[0043] Example 1 <Spherical filler> The spherical silica (B1) has an average primary particle diameter D1 of 1.9 μm and a specific surface area of 1.7 m 2The spherical silica (B2) was prepared by using spherical silica particles having an average primary particle diameter D2 of 0.6 μm and a specific surface area of 5.6 m. 2 The spherical silica particles were obtained by synthesizing the particles by a method in which a chemical flame is formed by a burner in an atmosphere containing oxygen, a metal powder that forms part of the target oxide particles is added to the chemical flame in an amount sufficient to form a dust cloud, and oxide particles are obtained by causing a deflagration, that is, by the VMC method (Vapourized Metal Combution Method) (JP Patent Publication No. 1-55201), and then surface-treating the particles with an organosilane. The average particle size of the spherical silica particles was measured by a laser diffraction / scattering method using a laser analysis particle size distribution analyzer.
[0044] <Production of Resin Composition Pellets> As the thermoplastic resin (A), 100 parts by mass of "Hashloy HS200E" which is an alloy (PC / ABS) of polycarbonate resin and ABS resin manufactured by Techno UMG Co., Ltd., 8.3 parts by mass of the above-mentioned spherical silica (B1), 3.6 parts by mass of the above-mentioned spherical silica (B2), and 37.3 parts by mass of carbon fiber "Teijin Tenax-J HTC422" (average length: 6 mm, average diameter: 1 μm) manufactured by Teijin Limited as the fibrous filler (C) were blended and uniformly mixed in a tumbler mixer. Using a twin-screw extruder "TEX30α" manufactured by Japan Steel Works, Ltd., the mixture obtained at a cylinder setting temperature of 220 ° C., a screw rotation speed of 80 rpm, and a discharge rate of 3.6 kg / hr was fed into the extruder from the barrel at the upstream of the extruder, melt-kneaded, and then cut to obtain resin composition pellets. The average length and average diameter of the fibrous filler (C) were determined by observing the cross section of the resulting resin composition pellets under a microscope, measuring each at 10 points, and averaging the measurements.
[0045] <MFR of resin composition> The MFR (g / 10 min) of the obtained resin composition pellets was measured under conditions of 230° C. and a load of 98 N in accordance with ISO 1133. The results are shown in Table 1.
[0046] <Linear expansion coefficient in flow direction> The linear expansion coefficient of the molded product was measured according to JIS K7197 as follows. The resin composition pellets were injection molded using an injection molding machine "SE75DU" manufactured by Sumitomo Heavy Industries, Ltd. at a cylinder setting temperature of 270°C, a mold setting temperature of 100°C, an injection speed of 40 mm / s, a holding pressure of 80 MPa, a holding time of 2 seconds, and a cooling time of 15 seconds to obtain a dumbbell-shaped molded product, which was then cut into a rectangular column having a length of 10 mm and a side length of 5 mm to prepare a test piece. The linear expansion coefficient of the obtained test piece in the machine direction (MD) was measured under the following conditions. The results are shown in Table 1. Measuring device: Hitachi High-Technologies Corporation "TMA TA7000" Measurement temperature: -40℃ to 80℃ Heating rate: 5℃ / min
[0047] <Production of molded products> The resin composition pellets were injection molded using an injection molding machine "SE75DU" manufactured by Sumitomo Heavy Industries, Ltd. at a cylinder setting temperature of 270°C, a mold setting temperature of 100°C, an injection speed of 40 mm / s, a holding pressure of 80 MPa, a holding pressure time of 2 seconds, and a cooling time of 15 seconds (mold dimensions: length 151.11 mm, width 101.06 mm, thickness 2.00 mm) to obtain a plate-shaped test piece having a length of 150 mm, a width of 100 mm, and a thickness of 2 mm.
[0048] <Moldability> The obtained test pieces were visually observed and then evaluated according to the following criteria. A: There was no warping, and the surface was smooth and had a good appearance. B: There is a slight warp or the surface is slightly uneven. C: Large warpage or numerous irregularities were found on the surface
[0049] <Painting of molded products> The paint "EC-MH62-1806SG" manufactured by Musashi Paint Co., Ltd., the hardener "Z-EC-H760", and the thinner "Z-K139" were mixed in a mass ratio of 100:40:100, and sprayed onto the test piece obtained in the above "Production of Molded Article" using a paint gun "T2AGPV" manufactured by Devilbiss, and then dried at 80°C for 30 minutes to paint the molded article (film thickness 15 μm). The appearance of the molded article after painting was visually observed and evaluated according to the following criteria. (Surface unevenness) A: There was no unevenness at all. B: There were one or two uneven spots. C: Overall unevenness (Item) A: There was no product at all. B: There were a few items. C: There were lumps all over the place.
[0050] <Manufacture of molded parts for automobile interiors> The resin composition pellets were injection molded using an injection molding machine "SE75DU" manufactured by Sumitomo Heavy Industries, Ltd. at a cylinder setting temperature of 270°C, a mold setting temperature of 100°C, an injection speed of 40 mm / s, a holding pressure of 80 MPa, a holding pressure time of 2 seconds, and a cooling time of 15 seconds to obtain a panel for an in-vehicle monitor having the shape shown in Figure 1 (length 151.03 mm, width 812.37 mm, thickness 14 mm).
[0051] <Durability of automotive interior parts> The glass parts of a monitor with a shape corresponding to the openings were fitted into the left and right openings of the obtained panel, and the panel and glass were fixed with double-sided tape. The obtained composite was heated and cooled 500 times, with one cycle being "heated to 80°C at a rate of 0.5°C / sec, held at 80°C for 1 hour, cooled to -30°C at a rate of 0.5°C / sec, and held at -30°C for 1 hour." The boundary between the panel and the glass part was visually observed, and durability was evaluated according to the following criteria. A: There was no peeling or gap at the boundary between the panel and the glass. B: Peeling or gaps occurred in one or two places at the boundary between the panel and the glass. C: Peeling or gaps occurred across the entire boundary between the panel and the glass.
[0052] <Impact resistance of automotive interior parts> The panel obtained in the above "Production of molded articles for automobile interiors" was dropped from a height of 50 cm, and then the panel was visually observed and evaluated according to the following criteria. A: No cracks were observed and the appearance was good. B: There were some cracks. C: The panel was cracked and damaged.
[0053] Example 2 A resin composition and a molded article were produced and evaluated in the same manner as in Example 1, except that 125 parts by mass of "Hashloy HG230E," an alloy of polycarbonate resin and ABS resin (PC / ABS) manufactured by Techno UMG Co., Ltd. containing 20% by mass of glass fibers having an average length of 0.6 mm and an average diameter of 15 μm, 21.9 parts by mass of the spherical silica (B1), and 9.4 parts by mass of the spherical silica (B2) were blended and mixed uniformly in a tumbler mixer and fed to a twin-screw extruder. The results are shown in Table 1.
[0054] Example 3 The resin composition and the molded article were produced and evaluated in the same manner as in Example 2, except that the amounts of the spherical silica (B1) and the spherical silica (B2) were adjusted so that the resin composition had the composition shown in Table 1. The results are shown in Table 1.
[0055] Comparative Examples 1 and 2 Molded articles were produced and evaluated in the same manner as in Example 1, except that instead of the resin composition pellets, "Cerivo LCF-1015" (Comparative Example 1) manufactured by Teijin Limited, which is a polycarbonate containing 25% by mass of long carbon fibers (average length: 3 mm, average diameter: 6 μm), or "Iupilon FGH3140F2" (Comparative Example 2) manufactured by Mitsubishi Engineering Plastics Corporation, which is a polycarbonate containing 40% by mass of glass fibers (average length: 0.3 mm, average diameter: 5 μm) were used. The results are shown in Table 1.
[0056] Comparative Examples 3 to 7 Resin compositions and molded articles were produced and evaluated in the same manner as in Example 2, except that the compounding ratios of the thermoplastic resin (A), the spherical silica (B1), the spherical silica (B2) and the fibrous filler (C) were changed as shown in Table 1. The results are shown in Table 1.
[0057] [Table 1]
Claims
1. Contains 100 parts by mass of a thermoplastic resin (A), 3 to 150 parts by mass of a spherical filler (B), and 3 to 100 parts by mass of a fibrous filler (C); The spherical filler (B) is composed of spherical silica (B1) having an average particle diameter D1 of 1 to 10 μm and spherical silica (B2) having an average particle diameter D2 of 0.1 to 3 μm, The ratio (D1 / D2) of the average particle diameter D1 (μm) to the average particle diameter D2 (μm) is 2 or more; A resin composition, in which the mass ratio (B1 / B2) of the spherical silica (B1) to the spherical silica (B2) is 10 / 90 to 90 / 10.
2. The resin composition according to claim 1, wherein the fibrous filler (C) is at least one selected from the group consisting of glass fibers and carbon fibers.
3. A molded article obtained by injection molding the resin composition according to claim 1 or 2.
4. The molded article according to claim 3, having a linear expansion coefficient in the machine direction (MD) of 40 ppm / °C or less.
5. A composite comprising the molded article according to claim 3 and a member made of at least one material selected from the group consisting of glass, ceramics and metals.
6. The molded article according to claim 3, which is for an automobile.
7. An in-vehicle monitor using the composite according to claim 5.
8. A method for producing a molded article, comprising injection molding the resin composition according to claim 1 or 2.
9. A method for producing a composite, comprising: obtaining a molded article by injection molding the resin composition according to claim 1 or 2; and then combining the molded article with a member made of at least one material selected from the group consisting of glass, ceramics, and metals.
Citation Information
Patent Citations
Molding material and molded article
JP2016088987A